Insight into the cellular involvement of the two reverse gyrases from the hyperthermophilic archaeon Sulfolobus solfataricus - Couturier, Mohea (BioMed Central, 2014)
BACKGROUND: Reverse gyrases are DNA topoisomerases characterized by their unique DNA positive-supercoiling activity. Sulfolobus solfataricus, like most Crenarchaeota, contains two genes each encoding a reverse gyrase. We showed previously that the two genes are differently regulated according to temperature and that the corresponding purified recombinant reverse gyrases have different enzymatic characteristics. These observations suggest a specialization of functions of the two reverse gyrases. As no mutants of the TopR genes could be obtained in Sulfolobales, we used immunodetection techniques to study the function(s) of these proteins in S. solfataricus in vivo. In particular, we investigated whether one or both reverse gyrases are required for the hyperthermophilic lifestyle. RESULTS: For the first time the two reverse gyrases of S. solfataricus have been discriminated at the protein level and their respective amounts have been determined in vivo. Actively dividing S. solfataricus cells contain only small amounts of both reverse gyrases, approximately 50 TopR1 and 125 TopR2 molecules per cell at 80°C. S. solfataricus cells are resistant at 45°C for several weeks, but there is neither cell division nor replication initiation; these processes are fully restored upon a return to 80°C. TopR1 is not found after three weeks at 45°C whereas the amount of TopR2 remains constant. Enzymatic assays in vitro indicate that TopR1 is not active at 45°C but that TopR2 exhibits highly positive DNA supercoiling activity at 45°C. CONCLUSIONS: The two reverse gyrases of S. solfataricus are differently regulated, in terms of protein abundance, in vivo at 80°C and 45°C. TopR2 is present both at high and low temperatures and is therefore presumably required whether cells are dividing or not. By contrast, TopR1 is present only at high temperature where the cell division occurs, suggesting that TopR1 is required for controlling DNA topology associated with cell division activity and/or life at high temperature. Our findings in vitro that TopR1 is able to positively supercoil DNA only at high temperature, and TopR2 is active at both temperatures are consistent with them having different functions within the cells.